EFFECTS OF P-ADDITION ON MAGNETIC-INTERACTIONS AND MICROSTRUCTURES IN CO-CR-P-PT MAGNETIC THIN-FILMS - SOHN, HK; SHIN, KH; LEE, TD; KANG, T; SUNG, CM (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 1995)
We have studied the effects of P addition in. a new alloy system of Co-Cr-P-Pt with the coercivity higher than 2600 Oe even when they were deposited without substrate heating and bias voltage. The addition of P increased the Co{1010} texture and decreased the Co{0002} texture, which is one of the reasons for the higher in-plane coercivity. The magnetization reversal mechanism changed from domain wall motion to curling type incoherent rotation with the addition of P. As the P content increases, delta M gradually shifts from positive to negative. This can be associated with enhancement of grain isolation and the reduction of out-of-plane orientation with the addition of P.
Keywords: MEDIA